Integration of Health, Economy, and Education in The Development of Women- and Child-Friendly Villages in Juwiring Village, Klaten - Abdiel Amanullah; Abdul Aziz Al Musthofa; Anisa Mifta Khaira; Gladis Niagustin Ilham (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Syarifuddin Lumajang, 2025)
This article describes the integration of health, economic, and education programs in an effort to create a Women and Child Friendly Village (DRPPA) in Juwiring Village, Klaten Regency. The approach used was Participatory Rural Appraisal (PRA) through intensive assistance with the community for approximately one year. Data were collected through participatory observation, focus group discussions, and activity documentation, then analyzed descriptively. The results show that the integration of these three areas was realized in the form of training in aromatic candle making and financial literacy for women; Al-Qur'an Education Park (TPA), tutoring, and finger painting for children; as well as mass gymnastics and Posbindu as a form of family health promotion. These activities increased the knowledge and participation of women and children, expanded access to basic services, and strengthened protection networks at the village level. This article recommends strengthening cross-sectoral coordination, sustainable village fund allocation, and DRPPA indicator-based monitoring to maintain program sustainability.